2017
DOI: 10.1002/jcp.25768
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for adiponectin‐mediated development of endometrial luminal epithelial cells during the peri‐implantation period of pregnancy

Abstract: Adiponectin is one of the adipokines in the collagen superfamily. It is secreted primarily by white adipocytes and influences reproductive processes including ovarian and uterine functions. Adiponectin regulates energy homeostasis, insulin sensitivity, and is anti-inflammatory in various tissues. Its receptors (ADIPOR1 and ADIPOR2) are widely expressed in mammalian tissues, including porcine conceptuses and endometrial during the estrous cycle and peri-implantation period of pregnancy. However, regulatory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…On the other hand, the latest studies revealed that adiponectin significantly stimulated proliferation and suppressed apoptosis of porcine uterine luminal epithelial cells (LEc) which would enhance uterine receptivity for embryo implantation. The mentioned adiponectin-stimulated proliferation of LEc was related to activation of the phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase signal transduction pathways [38]. This finding supports the hypothesis that adiponectin signalling is necessary for the establishment and maintenance of conceptus–uterine cross-talk during early pregnancy.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, the latest studies revealed that adiponectin significantly stimulated proliferation and suppressed apoptosis of porcine uterine luminal epithelial cells (LEc) which would enhance uterine receptivity for embryo implantation. The mentioned adiponectin-stimulated proliferation of LEc was related to activation of the phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase signal transduction pathways [38]. This finding supports the hypothesis that adiponectin signalling is necessary for the establishment and maintenance of conceptus–uterine cross-talk during early pregnancy.…”
Section: Discussionsupporting
confidence: 55%
“…ER stress in adipose tissue of obese women with gestational diabetes mellitus results in an increase in interleukin‐1β, IRE1α, GRP78, and X‐box binding protein 1 (XBP1) (Liong & Lappas, ). We previously reported increased expression of UPR‐regulatory genes in response to tunicamycin treatment of pLE cells (Lim, Choi, Bae, Bazer, & Song, ). Based on those results, we confirmed effects of BDNF on the tunicamycin‐induced ER stress in pLE cells and demonstrated that tunicamycin induced death of pLE cells involved an increase in cells in the Sub‐G 1 phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 98%
“…ER stress activates three highly conserved signaling cascades in the UPR stress sensors, including PERK that in turn phosphorylates eIF2α and ATF6α, which increase GRP78 to enhance folding capacity, and IRE1α which in turn activates X‐box binding protein 1 (Hetz, ). In domestic animals, tunicamycin‐induced ER stress decreases proliferation of porcine uterine luminal epithelial cells and increases the expression of ER stress response proteins implicated in implantation failure during early pregnancy (Lim, Bae, Bazer, & Song, ; Lim, Choi, Bae, Bazer, & Song, ). Moreover, ER stress signaling may be associated with mammary lipogenesis during lactation in dairy cows, with accumulation of PERK protein within the ER cisternae (Invernizzi, Naeem, & Loor, ).…”
Section: Discussionmentioning
confidence: 99%